Immortality and Rebirth in Jade: A White Jade Cicada from the Han Dynasty (202 BCE–220 AD) at the Royal Ontario Museum - He, Zhiying (The Columbia Journal of Asia, 2025)
This paper examines a white jade cicada from the Han Dynasty (202 BCE–220 CE) in the Royal Ontario Museum in Toronto, exploring its material, symbolic, and ritual significance within early Chinese funerary culture. The cicada is an insect associated with periodic molting, and it has become a metaphor for rebirth and immortality. During the Han Dynasty, cicadas were carved in jade or other stones and placed on the tongues of the deceased, signifying the preservation of the soul and the wish of rebirth. Methodologically, the paper integrates archaeological contextual analysis with textual analysis of Han Dynasty classics, such as the Book of Rites (Liji) and Huainanzi. It places the jade cicada within both Daoist beliefs and Confucian frameworks of filial piety. A comparative analysis of this artifact alongside twenty-one cicadas in the ROM collection, dating from the Shang to Qing dynasties, allows for a broader understanding of the material choices and craftsmanship of this specific jade cicada. By comparing jade cicadas with examples made of glass or stone, the paper highlights how material quality and carving techniques reinforced social hierarchies in funerary practice and how the deceased's social status was associated with the materiality. The paper further investigates the role of jade’s materiality, including its durability, beauty, and philosophical implications, and explores its function as an elite funerary object. Through the close examination of the materiality of white Hetian jade, which was imported via the Silk Road, the paper finally explores the cultural exchange in the Han. Ultimately, the jade cicada served dual functions: for the deceased, it showed their wishes of immortality and rebirth; for the living, it expressed their filial piety to their family members through the use of precious materials. Through the perspective of material culture, this single artifact thus reflects a broader social and cultural background in Han Dynasty China.